Surface Water Price to Improve Caisim Farming Efficiency in Tabanan Regency, Indonesia - Dananjaya, I Gusti Agung Nyoman; Dewi, Kadek Ayu Charisma Julia; Paramarta, Pande Made Ari Ananta; Miyazawa, Naori (HABITAT, 2024)
Objective of this research is to analyze the price of surface water at the South Yeh Panan Dam in an effort to increase the efficiency of caisim farming in Tabanan Regency. Subak Bengkel is the largest subak in Kediri District, Tabanan Regency with an area of 329 Ha. In addition to planting rice, farmers in Subak Bengkel also plant other commodities, namely caisim with an average planting area of 40 Ha/season). The method used in research on surface water price analysis at the South Yeh Panan Dam in an effort to increase the efficiency of lowland caisim farming in Tabanan Regency is value of marginal product analysis. Data analysis with regression using the SPSS 22 software program, the regression coefficient value (b) will be obtained.i) of each input factor which also shows the magnitude of the elasticity value. The price of water in Subak Bengkel based on Value of Marginal Product (VMP) analysis is IDR. 1,438,164.62/ha/season or IDR 30,402.80/m3/season. This price is a contribution given by water resources to the production of caisim farming in Subak Bengkel so that farmers need to utilize water resources that have been given free by nature efficiently and wisely. Farmers are expected to utilize water resources that have been given freely by nature efficiently and wisely.